Impact of operator and site experience on outcomes after angioplasty and stenting in the SAMMPRIS trial. (12th September 2012) - Derdeyn, Colin P; Fiorella, David; Lynn, Michael J; Barnwell, Stanley L; Zaidat, Osama O; Meyers, Philip M; Gobin, Y Pierre; Dion, Jacques; Lane, Bethany F; Turan, Tanya N; Janis, L Scott; Chimowitz, Marc I; et al.
Abstract : Background and purpose: To investigate the relationship between physician and site experience and the risk of 30 day hemorrhagic and ischemic strokes in the stenting arm of the Stenting and Aggressive Medical Management for the Prevention of Recurrent Ischemic Stroke (SAMMPRIS) trial. Methods: Study records and an investigator survey were examined for physician and site related factors, including: number of Wingspan and aneurysm stents submitted for credentialing, number of study procedures performed in SAMMPRIS, years in practice after training, primary specialty, and site enrollment. Bivariate and multivariate analyses were performed to determine if these factors were associated with the 30 day rate of cerebrovascular events after angioplasty and stenting. Results: 213 patients underwent angioplasty alone (n=5) or angioplasty and stenting (n=208) with study devices by 63 interventionists at 48 sites. For credentialing, the median number of Wingspan and similar aneurysm stent cases submitted by study interventionists were 10 and 6, respectively. Interventionists with higher numbers (>10) of Wingspan cases submitted for credentialing tended to have higher rates of 30 day events (19.0% vs 9.9%) than those with <10 cases. High enrolling sites in the trial tended to have lower rates of hemorrhagic stroke (9.8% at sites enrolling <12 patients vs 2.7% at sites enrolling > 12 patients). Conclusions: Interventionists credentialed with less Wingspan experience were not responsible for the high rate of periprocedural stroke in SAMMPRIS. Hemorrhagic stroke may be related to low enrollment in the trial but not previous Wingspan experience.